Age and estrogen-associated reductions in hypoxic ventilatory response and chemosensitivity in female rats - Grittner, Jessica M. L.; Barok, Rebecca; Juarez Lopez, Edgar; Shah, Misha; Dougherty, Brendan J. (Frontiers in Physiology, 2025)
Respiratory function is modulated by circulating steroid hormones. In female rats, steroid hormones fluctuate across the normal estrous cycle and decline with age, similar to human menopause. To determine the influence of steroid hormones, and mimic aspects of age-related reductions in hormones, the ovariectomy model is often employed. Ovariectomy (OVX) induces an immediate and persistent decrease in steroid hormones. The current study aimed to interrogate whether the OVX model of hormone reduction impacted specific aspects of respiratory function [chemosensitivity and the hypoxic ventilatory response (HVR)] in a manner consistent with natural age-related declines in hormones. Using barometric plethysmography, three experimental groups of female rats were assessed for HVR, chemosensitivity, and respiratory neural drive during progressive hypoxic challenges (FIO2: 0.15, 0.12, and 0.09): young (3–5 mos. old; in proestrus; n = 10), young OVX (3–5 mos. old; n = 10), and aged (>20 mos. old; n = 10). Our findings indicted that sex hormone loss did not appear to impact chemosensitivity or neural drive. Natural aging, but not OVX, resulted in decreased HVR as well as reduced magnitude in ventilatory output during stepwise hypoxia. Differences in metabolism were important to the interpretation of these results. Collectively, these data support the concept that aging impacts female respiratory function in complex and unique ways that differ from OVX.